Representasi Analisis Kebebasan dan Penjara Sosial dalam Tayangan Film Barbie - Puteri Andanie, Salma; Gusthini, Misyi (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2024)
This study analyzes how the film Barbie depicts freedom and social constraints, focusing on how these themes emerge through the characters and story. The aim of this analysis is to provide an understanding of how Barbie reflects modern issues related to identity, empowerment, and the challenges of achieving true freedom in a society filled with rules. As Greta Gerwig (2023) stated,